Developments in structural system reliability assessments of fixed steel offshore platforms - Onoufriou, Toula; Forbes, V.J (My University, 2001)
In recent years there have been significant developments in the area of system reliability assessments which are becoming increasingly important given the framework of the ‘goal setting’ regime and other changes that are taking place within the offshore industry. The objective of this paper is to review and critically examine recent developments in system reliability methods for fixed steel offshore platforms specifically and identify areas that need to be examined further to maximise the benefits from the use of these techniques. The paper examines the range of proposed methods for system reliability assessment of fixed steel offshore structures under extreme environmental loading. The associated characteristics of the various methods are examined and the paper concentrates in particular on the treatment of the resistance. The various system effects including both deterministic and probabilistic effects and their relative contribution to the overall system reliability are addressed. Key issues such as the modelling uncertainties and sensitivities, validation and benchmarking of the proposed methods are also examined. The study also highlights a number of technical and philosophical issues which need to be addressed to increase the benefits from system reliability applications in design and re-assessment of fixed platforms.
Keywords: Offshore structures; Reliability; Structural analysis (Engineering)